PENGARUH PENGEMBANGAN SDM DAN KEPRIBADIAN TERHADAP KOMPETENSI DAN PRESTASI KERJA KARYAWAN PADA PT. BARATA INDONESIA DI GRESIK - H. Edy Sutrisno (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
In the effort to win competitions, organizations can improve their employee’s performance by developing their human resources and personality. For that reason, this research is to analyze the impact of development of human resources and personality toward competence and employee’s performance.This is a quantitative research. 150 employees of PT. Barata Indonesia participated in this study. The data were collected using questionnaires and analyzed using path analysis, which were processed using AMOS. The result reveals that (1) human resources development have a positive effect to competence, (2) personality development have a positive effect to competence, (3) human resources development significantly have a positive effect on to employee’s performance, and (4) personality development have a positive effect to employee’s performance. Hopefully, this research might complete the previous studies and could be useful for the company to determine its policy directions in developing their human resources and personality, and it also can make the company to survive from the higher industrial competition